1996
DOI: 10.1103/physrevd.53.722
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Lorentzian wormholes

Abstract: Evolving Lorentzian wormholes with the required matter satisfying the energy conditions are discussed. Several different scale factors are used and the corresponding consequences derived. The effect of extra, decaying (in time) compact dimensions present in the wormhole metric is also explored and certain interesting conclusions are derived for the cases of exponential and Kalusa-Klein inflation.PACS number(s): 04.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
138
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 24 publications
4
138
0
Order By: Relevance
“…Lorentzian wormholes in spacetimes with more than four dimensions were analyzed by several researchers [22,23]. In particular, wormholes in Einstein-Gauss-Bonnet gravity were considered in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Lorentzian wormholes in spacetimes with more than four dimensions were analyzed by several researchers [22,23]. In particular, wormholes in Einstein-Gauss-Bonnet gravity were considered in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In their model, the wormhole initially inflates and later evolves like a FRW spacetime thereby implying our Universe to be an evolving wormhole. Later Anchordoqui et al [26] extended the previous work [25] by choosing the non-zero redshift function and obtained evolving wormhole solutions with nonexotic matter. Arellano & Lobo [27] found contracting wormhole solutions within non-linear electrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Kar & Sahdev had shown that if the wormhole spacetime is taken to be evolving (non-static) than the matter threading the wormhole geometry need not to be WEC violating [25]. In their model, the wormhole initially inflates and later evolves like a FRW spacetime thereby implying our Universe to be an evolving wormhole.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages and potential of this geometrical approach in finding new solutions in general relativity form the discussion of Section 5. In that section, we show explicitly how this geometrical technique yields the derivation of the metric for an inflationary wormhole with a conformal factor, which was taken to be an ansatz in [3][4][5]. We then conclude this paper in Section 6.…”
Section: Introductionmentioning
confidence: 99%